Boundary lost : postcards from New Albion : an exegesis presented in partial fulfilment of the requirements for the postgraduate degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Jago, Alexander (Massey University, 2025)
Boundary Lost is a lyrical documentary photographic project, interrogating themes related to memory, meditating on how we interact with our physical and social environment. Through the exploration of architecture and landscape, I explore capitalist notions of commodification and colonial history as they sit within the built environments and landscapes of Aotearoa. This project draws heavily from and is influenced by my Pākehā upbringing and historical research into the colonisation of Aotearoa. My work is explicitly an exploration of the world I know, the landscape in which I grew up and have lived in for many years. The work affords an audience the opportunity to consider the remnants of a ‘dying empire’ that litter the small and medium sized towns of our country. Drawing from the relics of once prosperous towns and industry, Boundary Lost is a collection of ambiguous locations that come together to create a sense of commonality, forming common language through the creation of the colonial landscape. With this work, I explore how colonisation has shaped the built environment with cultural and capitalistic enterprise and conversely how the landscape has pushed back upon it. I am asking ‘if we hold our landscape in such high reverence, why are we so blind to the inequalities of our people and infrastructure?’. The use of traditional photographic methods both nods toward a historical positioning and also offers the most meditative practice for myself as the photographer. The role of Pākehā culture is particularly relevant in the context of the increasingly conservative and reactionary stance of our current Government. The weaponisation of anti-intellectualism and anti-Māori rhetoric, reflects a colonial settler mentality, prioritising the perceived supremacy of British and imperialist traditions. Increasingly dictated to by neo-liberal imperialism, it is important to confront and examine the role of colonisation in the formation and influence in Pākehā identity. Boundary Lost navigates the journey of understanding the role of colonisation on the national image of New Zealand and how this identity emerges from the human landscape.
Figures are reproduced with permission.
Keywords: 360604 Photography, video and lens-based practice